Determinants of health behaviors in individuals of medical and non-medical professions - Nowicki, Grzegorz Józef; Ślusarska, Barbara; Rudnicka-Drożak, Ewa; Wiśniewska, Anna; Jędrzejkiewicz, Bernadeta; Pielaszkiewicz, Kamil; Sekut, Aleksandra (Nursing in the 21st Century, 2018)
DETERMINANTS OF HEALTH BEHAVIORS IN INDIVIDUALS OF MEDICAL AND NON-MEDICAL PROFESSIONSAim. Determination of health behaviors in the group of people performing medical and non-medical professions.Material and methods. The research covered 598 individuals divided into two groups: those performing medical professions (group M, n = 305) and non-medical (group P; n = 293). Standardized tools were used: Health Behavior Inventory, Multidimensional Health Locus of Control Scale - version B, General Self-Efficacy Scale on risk factors and prevention of civilization diseases (own authorship). The controls were subjected to measurement of blood pressure as well as their height and body mass tests.Results. In group M, the level of self-efficacy, the location of health control in terms of the influence of the others and the chance, age, incidence of cardiovascular diseases in the father, smoking and the level of mean systolic blood pressure explain 17.5% of the variability of health behavior. In group P, the level of self-efficacy, location of health control in terms of the influence of the others and the chance, monthly net income per a family member, the occurrence of neoplasms in siblings, smoking, average blood pressure and the level of knowledge about risk factors and prevention of civilization diseases explain 27.9% of the variance of the health behavior variable.Conclusions. There is a diversification of selected determinants of health behaviors in the group of individuals performing medical and non-medical professions, with their stronger impact on non-medical professionals (17.5% vs. 27.9% of their variability).